Kajian Hukum tentang Pengalihan Benda Jaminan Fidusia Tanpa Persetujuan Tertulis dari Penerima Fidusia: (Studi Kasus Putusan Nomor 244/Pid.Sus/2021/PN. Grt) - Mardiman Sane; Hotman Sinambela (CV Rewang Rencang, 2025)
Abstract The transfer of fiduciary collateral objects without the creditor's approval is still often carried out by debtors, which according to the provisions cannot be done without the creditor's approval but is still carried out by the debtor, where when the debtor has difficulty paying off his receivables, there is no longer a collateral object that can be executed by the creditor in lieu of paying off the receivables. debtor. The formulation in this research is how to apply the law to perpetrators of criminal acts of transferring objects that are the object of fiduciary collateral without the written consent of the fiduciary recipient and what the judge's legal considerations are in handing down decisions regarding the transfer of objects that are the object of fiduciary collateral without the written consent of the fiduciary recipient in decision number 244/Pid.Sus/2021/PN Grt. The research method used in this research is a normative juridical research method. The normative juridical approach isan approach based on the main legal material by examining theories, concepts, legal principles and statutory regulations related to this research. Furthermore, based on the provisions in Article 36 of the Fiduciary Law, a Fiduciary Giver who transfers, pawns or rents out objects that are the object of Fiduciary Guarantee as intended in Article 23 paragraph (2) without prior written approval from the Fiduciary Recipient, will be punished with a crime. maximum imprisonment of 2 (two) years and a maximum fine of IDR 50,000,000 (fifty million rupiah). And the judge's legal considerations in handing downthe verdict in Decision Number 244/Pid.Sus/2021/PN Grt refer to the article charged by the public prosecutor against the defendant under Article 36 Jo. Article 23 paragraph (2) Law No. 42 of 1999 concerning Fiduciary Guarantees. Based on the facts revealed during the trial, the Judge concluded that all the elements of the article were fulfilled so that the defendant was legally and convincingly proven guilty of committing the crimi al act of transferring objects that were the object of fiduciary collateral without the written consent of th e Fiduciary Recipient.